The Effects of Self Efficacy and Self Regulated Learning to Academic Achievement - Fajar Pandu Nugroho; Syarifudin Tippe; Darma Rika Swaramarinda (Winaya Inspirasi Nusantara Foundation, 2020)
The purpose of this study was conducted to determine the effect between self-efficacy and self-regulated learning to academic achievement in students of class X SMKS 3 Taman Siswa Central Jakarta. This research was conducted for two months, that is from May to June 2018. The method used in this research is survey method. The population in this study were all students of SMKS 3 Taman Siswa Central Jakarta amounting to 136 students. With reference on the table Isaac and Michael the number of samples in this study as many as 95 respondents. The coefficient of determination t calculation on Self efficacy variables of 2.392 and t count on Self-Regulation in Learning variables of 2.276. Where t table of 1.986, it can be concluded self-efficacy variables and self-regulation in learning has a significant positive effect on academic’s achievement. Because t coount > t table. for Test F, found Fcount equal to 14,809> Ftable equal to 3,10. This means there is a simultaneous influence between Self Efficacy and SelfRegulation variables in Academic Achievement because Fcount> Ftable. Multiple regression equation obtained result Ŷ = 68,043 + 0,4128X1 + 0,052X2. The coefficient value of determination R2 is 0,244. This means selfefficacy variables (X1) and Self-Regulated Learning (X2) on Achievement Learning (Y) as much as 24,4%.